Control of a flexible manipulator with noncollocated feedback: time-domain passivity approach - Jee-Hwan Ryu; Dong-Soo Kwon; Hannaford, B. (IEEE transactions on robotics, 2004)
A new method to control a flexible manipulator with noncollocated feedback is proposed. We introduce a method to implement the time-domain passivity-control approach to a flexible manipulator with noncollocated feedback, which could not be treated with the previous time-domain passivity-control framework due to a possible active transfer function from the input to the noncollocated output. The proposed method is simulated with a single-link flexible manipulator, and a good control performance is obtained.